Online Survey Application System Design Via Telegram at the Bsa Project Surabaya Company - Wahyu Ardian Saputro; Mohammad Suryawinata (Procedia of Engineering and Life Science, 2021)
To improve the quality of service at BSA Project companies, it is necessary to survey how the results of the performance of BSA Project employees in serving customers, so that the results of the survey can be a company benchmark in evaluating and correcting if an error occurs. Making an Online Survey Application System Via Telegram at the BSA Project Surabaya Company which can be one of the benchmarks for companies to monitor and evaluate the performance of employees for service to customers. Supporting subjects in making this application are all employees in the Surabaya BSA Project Company. The application of the online survey application can be implemented using a php server. This online survey web application can also be connected to the telegram application, and the results can be displayed in real time. Testing the basic functions of the system that is done directly can be concluded that this application program can run as expected, then the results of the user acceptance test that has been tested on 20 employees can be known that the percentage for agreed responses is between 80% to 100 %, then the choice to disagree is between 0% to 20%, for that it can be concluded that the majority of user responses in using this application program are agreed and this application program can be well received by BSA Project Surabaya employees